DIGITAL SEHAT PUSKESMAS: PENGUATAN LITERASI DIGITAL UNTUK MENINGKATKAN KEPATUHAN PENGELOLAAN HIPERTENSI PADA MASYARAKAT DI PUSKESMAS WUA-WUA - Ruslin Ruslin; Asniar Pascayantri; Rachma Malina; Asriullah Jabbar; Nur Aviarahma Sihani; Rini Apriani; Siti Hayati; Uswatun Khasanah; Sumi Wally; Wa Ode Ifan Mustikawati; Anastasyah Putri; Yuyun Suria; Nasrudin Nasrudin; Muhammad Ilyas; Mubarak Mubarak (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Hypertension is a major public health problem that requires long-term management and high patient adherence, which remains a challenge at the primary health care level. This community service activity aimed to strengthen digital health literacy to improve hypertension management adherence among the community at Puskesmas Wua-Wua. The activity was conducted using a digital-based health education approach through direct counseling, distribution of educational leaflets equipped with QR codes, and evaluation using a comprehension questionnaire. The educational media contained information on hypertension management, medication adherence, and healthy lifestyle practices. The results showed that all participants positively accepted the digital literacy-based leaflet and perceived it as useful, easy to understand, and relevant to their needs. This activity indicates that integrating printed and digital educational media can effectively support hypertension management and strengthen promotive and preventive efforts in primary health care settings